통화정책의 불확실성은 주택가격에 영향을 미치는가? - 최차순(Choi, Cha Soon) (대한부동산학회지, 2022)
본 연구에서는 통화정책의 불확실성이 주택가격에 영향을 미치는지 여부를 확인하고자 MRS(Markov regime switching) 모형을 이용하여 실증분석하였다. 분석기간은 자료 입수가 가능한 1990년 1월부터 2021년 12월까지 이다. 분석 결과는 다음과 같다. 첫째, 샘플분 석기간의 변동성이 높은 국면 2에서 MPU(Monetary Policy Uncertainty) 지수가 높아질 수록 주택매매가격에 부정적인 영향을 미치는 것으로 나타났다. 둘째, 글로벌금융위기후 기간에 변동성 낮은 국면 1과 변동성이 높은 국면 2에서 MPU 지수가 높아질수록 주택매매가격에 부정적인 영향을 미치는 것으로 나타났다. 셋째, MPU 지수는 주택가격이나 전세가격에 비대칭적으로 영향을 미치는 것으로 나타났다. 따라서 경제안정화를 위해서는 이자율 정책과 같은 전통적인 실물경제 안정화 정책뿐 아니라 MPU 지수와 같은 시장 심리요인도 정책 목표 관리 지표로 동시에 고려할 필요성이 있다. This paper empirically examines the impact of different regimes of monetary policy uncertainty(MPU) index on housing sales and jeonse price volatility covering the period from January 1990 to December 2021 with adopting Markov regime switching. The anaysis result can be summarized as following. First, During the sample analysis period, it is found that the higher the MPU index, the more negatively the housing sales price at the high volatility regime 2(expansion period). Second, it is found that the higher the MPU index, regardless of regimes, is to affect a negative effect on the housing sales price during the post-global financial crisis period. Third, It ia found that the MPU index reacted asymmetrically to housing prices or jeonse prices. Therefore, in order to stabilize the economy, it is necessary to simultaneously consider not only traditional real economy stabilization policies such as interest rate policies but also market psychological factors such as the MPU index as policy goal management indicators. KCI Citation Count: 0